MEDIA PEMBELAJARAN GAME PUZZLE BERBASIS ANDROID UNTUK MENINGKATKAN MINAT SISWA DALAM BAHASA INGGRIS - Destiani Iman, Finda; Usmanto, Budi; Tri Handayani, Lilis (YHMM PUBLISHING, 2024)
Learning English is one of the challenges in the world of education, especially in increasing student interest. The use of interactive and interesting learning media can be a solution to increase learning motivation. This study aims to design and develop learning media in the form of Android-based puzzle games as a means to increase student interest in learning English. The research methods used include needs analysis, design, development, and testing the effectiveness of games in increasing student interest in learning. Puzzle games are designed with interactive features, attractive graphics, and challenging but educational game mechanisms. Testing was carried out through limited experiments with high school students as respondents. The results of the study showed that the use of Android-based puzzle games in learning English was able to significantly increase student interest. Students are more enthusiastic in learning because the material is delivered in a more fun and less boring way. Thus, the development of Android-based educational games can be an alternative effective learning media in improving the quality of English learning in schools.